Trimodal electroencephalogram during isoflurane anaesthesia - Dimpel, Lorenzo (Journal of Neuroanaesthesiology and Critical Care, 2016)
The effects of common anaesthetic agents, such as isoflurane or propofol, on the electroencephalogram are well-known. The most characteristic feature is the marked increase in delta power and alpha power resulting in a bimodal power spectrum from light to moderately deep anaesthesia. Here, a case is presented where the power spectrum became trimodal when anaesthesia was lightened towards wake up. The implications of a third mode for depth-of-anaesthesia monitoring are discussed. Its neuro-physiology is unknown, as it has never been reported before.
Keywords: Anaesthesia; bimodal; electroencephalogram; trimodal